Dinuclear salen cobalt complex incorporating Y(OTf)(3): enhanced enantioselectivity in the hydrolytic kinetic resolution of epoxides - Patel, Deepak; Kurrey, Ganesh Ram; Shinde, Sandip S.; Kumar, Pradeep; Kim, Geon-Joong; Thakur, Santosh Singh (RSC Advances, 2015)
The activation of inactive Jacobsen's chiral salen Co(II) (salen = N,N'-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediamine) compound is attained by dinuclear chiral salen Co(III)-OTf complex formation with yttrium triflate. The yttrium metal not only displays a promoting effect on electron transfer, but also assists in forming two stereocentres of a Lewis acid complex with Co(III)-OTf. We found that the binuclear Co-complex significantly enhanced reactivity and enantioselectivity in the hydrolytic kinetic resolution of terminal epoxides compared to its analogous monomer and kinetic data are also consistent with these results.